Um modelo de dinâmica de sistemas para avaliação de cenários no processo de remanufatura de cartuchos de toners e impressoras - Antunes, Marcelo Cassanta (2022)
The increase in waste generation from information technologies and electricity consumption in Brazil shows the need to search for environmental and economic solutions. Product developers employ key strategies to solve this problem, namely efficient use of materials in the production of equipment, and the use of tools such as remanufacturing or recycling. Remanufacturing includes the use of industrial processes that extend the life of items that are worn out and unable to perform their original function. Remanufacturing operations have strengths and impasses arising from the process itself, and it is necessary to analyze these characteristics, consider themes and evaluate their application. The remanufacturing process consists of bringing an already worn out good to the same or superior quality as a new good with an equivalent guarantee. The benefits expand to environmental aspects, reducing electricity consumption at rates more than half compared to the traditional process, and significantly reducing the consumption of materials from nature. Remanufacturing makes it possible to improve the production process, reducing the environmental impact caused and production costs. Therefore, this dissertation presents the development of simulation models to evaluate the environmental and financial impacts caused by the extension of the life cycle of printers and toner cartridges through remanufacturing. For the modeling of the system, the System Dynamics methodology was used using the Vensim simulator, version 2022. For experimentation, verification and evaluation of the model, three scenarios were defined: the current one, with the current reuse rates, the optimistic, with high rates of waste reuse; and medium, with lower reuse rates. In designing the model, it was decided to build it in sub-models, in order to facilitate its experimentation and analysis. The results present important data for the application of remanufacturing, and the simulated scenarios justify the expansion of remanufacturing on a larger scale.